Avaliação ecotoxicológica da dipirona sódica em Oreochromis niloticus através de biomarcadores - Ribas, Eberton Luiz Aires (2022)
Emerging contaminants (EC) refer to a class of products increasingly present in ecosystems. It is known that the presence of these substances in environments have toxicological action, especially in aquatic environments. Among these contaminants, we can mention drugs, which often end up in water bodies, becoming persistent in these environments. Consequently, the organisms that live in these environments are vulnerable to the reactivity of the environment, which can result in mutagenic and morphological reactions, loss of their natural habitat and mortality. The present study investigated, through bioassays, the effects caused by the drug sodium dipyrone, in fish Oreochromis niloticus (Nile Tilapia), after subchronic water exposure for a period of 21 days, through analysis of genetic and biochemical biomarkers. Three drug sublethals concentrations were evaluated: 0.7; 4.9 and 34.3 mg/L, defined according to the literature. The renewal of water and drug was performed daily in the proportion of ¾ of the total volume of each aquarium. Two bioassays were carried out, under the same experimental conditions, in order to increase the number of organisms sampled. Statistical analyzes were performed using parametric and non-parametric methods. Genotoxicity was evaluated through the comet assay in blood and renal tissue cells, and in blood, a statistically significant difference was observed between the groups exposed to the three concentrations, in relation to the negative control group, in both bioassays. For renal tissue, the analysis of the genetic material of organisms in bioassay 1 showed a difference between the negative control group and the concentration of 34.3 mg/L, while in bioassay 2 a significant difference was observed between the three exposure groups and the negative control group. In the piscine micronucleus test, significant differences were found between the 4.9 mg/L and 34.3 mg/L exposure groups in relation to the negative control group, in both bioassays, characterizing a genotoxic action of the drug. AchE activity in muscle showed inhibition in animals exposed to the three concentrations of the drug, in both bioassays, while AchE activity in brain showed no change in relation to the negative control group. Regarding the activity of GST in the liver, there were differences between the groups of animals in bioassay 1: statistically significant differences between the negative control group and groups of exposure 4.9 and 34.3 mg/L; in bioassay 2 there was no difference between the groups analyzed. Fulton’s condition factor analysis showed that subchronic exposure to the evaluated concentrations of sodium dipyrone did not affect the general health of the animals. The results found in the present work demonstrate the potential ecotoxicological effect of the drug sodium dipyrone for the fish species O. Niloticus.